Parochial prosocial religions: Historical and contemporary evidence for a cultural evolutionary process. (7th March 2016) - Norenzayan, Ara; Shariff, Azim F.; Gervais, Will M.; Willard, Aiyana K.; McNamara, Rita A.; Slingerland, Edward; Henrich, Joseph
Abstract: In our response to the 27 commentaries, we refine the theoretical claims, clarify several misconceptions of our framework, and explore substantial disagreements. In doing so, we (1) show that our framework accommodates multiple historical scenarios; (2) debate the historical evidence, particularly about "pre-Axial" religions; (3) offer important details about cultural evolutionary theory; (4) clarify the term prosociality; and (4) discuss proximal mechanisms. We review many interesting extensions, amplifications, and qualifications of our approach made by the commentators.